Meningkatkan Hasil Belajar Peserta Didik Menggunakan Metode Diskusi Simposium pada Mata Pelajaran PAI di SMAN 1 Lunang - Nurhidayani, Nurhidayani (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to enhance students’ learning outcomes and engagement in Islamic Religious Education (PAI) through the implementation of the symposium discussion method. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The findings reveal a significant improvement in students’ learning outcomes, with average scores increasing from 84 in Cycle I to 88 in Cycle II. The classical learning completeness rose from 70% to 90%. Student engagement also improved, with active participation rates rising from 83.33% to 95%. The application of this method proved effective by integrating problem-based learning, interactive media, and active teacher facilitation. The study concludes that the symposium discussion method significantly enhances students’ learning outcomes and engagement